The Prevalence and Risk Factors for Polycystic Ovary Syndrome (PCOS) among Adolescents in Indonesia: Implications for Early Intervention - Habiburrahman Said; Rheina Weisch Fedre; Saurie Hernandez; Sophia Lucille Rodriguez; Fatimah Mursyid; Irna Nettles (Sriwijaya Journal of Obstetrics and Gynecology, 2024)
Introduction: Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting adolescents, with potential long-term health implications. This study aimed to determine the prevalence and identify risk factors associated with PCOS among Indonesian adolescents. Methods: A cross-sectional study was conducted involving adolescent girls aged 15-19 years from selected schools in Jakarta, Indonesia. Data were collected through questionnaires, physical examinations, and biochemical assessments. PCOS diagnosis was based on the Rotterdam criteria. Logistic regression analysis was used to identify risk factors associated with PCOS. Results: The prevalence of PCOS among Indonesian adolescents was found to be 6.5%. Significant risk factors associated with PCOS included obesity (OR=3.2, 95% CI 2.1-4.8), family history of PCOS (OR=2.5, 95% CI 1.6-3.9), irregular menstrual cycles (OR=4.1, 95% CI 2.8-6.0), and hirsutism (OR=2.8, 95% CI 1.9-4.2). Conclusion: PCOS is prevalent among Indonesian adolescents. Early identification of risk factors such as obesity, family history, irregular menstruation, and hirsutism is crucial for early intervention and management to mitigate potential long-term health consequences.